Problemer vedrørende den talmæssige belysning af betalingsbalancen for Grønland - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
– The balance of payments of Greenland has special features due to an important current transfer, bloktilskud, from Denmark. The trade balance does not exhibit a deficit of this order of magnitude but comparison of the bloktilskud and the deficit is difficult as official figures are available for the merchandise trade only. Figures for services are missing. However, guesses about the size of a deficit in the services' trade do not easily discard the impression of a large surplus on the current account. Over a ten year period it is suggested that accumulated surpluses could be twice the level of Greenland's GDP. This seems unlikely, but the available data raise a puzzle that ought to be addressed as it nourishes suspicion of unobserved accumulation of wealth.
hdl:10398/7550
Keywords: H00; 330; Greenland; Bloktilskud; Trade balance; GDP